Designing a Connected Sustainable Living Environment. (June 2013) - Kotsopoulos, Sotirios D.; Graybill, Wesley; Casalegno, Federico
This paper presents the design and development of a prototype, connected to a sustainable home project, which is at its final stage of implementation in Trento, N. Italy. The paper specifically focuses on the design ends and the technological means deployed in the process of implementing the prototype. Design ends outline the technical premises underpinning the development of the house systems. Technological means refer to the methods and technologies that had been deployed to satisfy the premises. Emphasis is given to the properties of the reconfigurable façade and the autonomous control system of the house, where variable transmittance materials, AI methods for building control and digital simulation are used in combination.